Distribution of chaetognaths in the Eastern Central Philippines with notes on the sexual maturity and diet of Flaccisagitta enflata (Grassi, 1881). - Noblezada, Mary Mar P. (College of Fisheries, University of the Philippines in the Visayas, 2008)
The spatial distribution, species composition and abundance of chaetognaths of the Eastern Central Philippines were investigated. The sexual maturity and diet of the most widespread species Flaccisgittaenflata (Grassi, 1881) were also examined. Thirty three specie of chaetognathsenflata were the most dominant and frequent species, comprising 54.7% and 23.9% respectively, of the total chaetognaths collected. The overall mean density was 1,061.2 ind. 100m-3. Highest density was recorded in the Visayan Sea while northern Bicol Shelf (NBS) and the rest of the internal waters showed low to moderately high densities. The region canbe subdivided into areas based on similarities in chaetognaths assemblages : the Pacific Inflow which is comprised of San Bernardino Strait and North Catanduanes stations, Bicol Shelf andVisayan Sea Shelf Margin which consist of stations in Ticao Pass and deep stations in the Visayan and Sibuyan Seas, and Visayan Sea Shelf which includes stations located in the innerand shallow portion of Visayan and south-eastern Sibuyan Sea. Temperature, salinity and stratification index were among the hydrographic factors influencing the distribution andabundance of chaetognaths. Immature Flaccisagittaenflata (stages I and II) were widely distributed throught the all areas surveyed and comprised 20-50% of the total individuals examined, while mature individuals (stages III and IV) appeared to be limited to the NBS and areas bordering the Vsayan Sea. Gut content analysis showed copepods were the predominant food organisms in the diet. High incidence of cannibalism was observed and a relatively high proportion of fish larvae and fish eggs were also noted in the gut. Flaccisagitta enflata can therefore be regarded as predator and competitor for food of fish and other marine fauna.